1991
DOI: 10.1104/pp.96.3.856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Indole-3-Acetic Acid and Indole-3-Butyric Acid on Internal Levels of the Respective Auxins and Their Conjugation with Aspartic Acid during Adventitious Root Formation in Pea Cuttings

Abstract: The influence of exogenous indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) on the internal levels of these auxins was studied during the first 4 days of adventitious root formation in cuttings of Pisum sativum L. The quantitations were done by high performance liquid chromatography with spectrofluorometric detection. IBA, identified by combined gas chromatography-mass spectrometry (GC-MS), was found to naturally occur in this plant material. The root inducing ability of exogenous IBA was superior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
6

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 27 publications
4
83
0
6
Order By: Relevance
“…The conversion of exogenous IAA to IAAsp appears to be a common process in plants. This process has been demonstrated in Pinus (Riov and Gottlieb, 1980), Dalbergia (Monterio et al, 1988), Vigna (Norcini and Heuser, 1988), Pisum (Nordstrom et al, 1991), and Lycopersicon (Catali et al, recently shown in Dalbergia (Ostin et al, 1992a), and based on cochromatography with an IAGlu standard in an HPLC system, it was tentatively identified in Cucumis both after IAA application (Purves and Hollenberg, 1982) and as an endogenous compound (Sonner and Purves, 1985). IAGluc formation after IAA addition has also been reported in Colchium (Zenk, 1961), Pinus (Riov and Gottlieb, 1980), and Lycopersicon (Catalá et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of exogenous IAA to IAAsp appears to be a common process in plants. This process has been demonstrated in Pinus (Riov and Gottlieb, 1980), Dalbergia (Monterio et al, 1988), Vigna (Norcini and Heuser, 1988), Pisum (Nordstrom et al, 1991), and Lycopersicon (Catali et al, recently shown in Dalbergia (Ostin et al, 1992a), and based on cochromatography with an IAGlu standard in an HPLC system, it was tentatively identified in Cucumis both after IAA application (Purves and Hollenberg, 1982) and as an endogenous compound (Sonner and Purves, 1985). IAGluc formation after IAA addition has also been reported in Colchium (Zenk, 1961), Pinus (Riov and Gottlieb, 1980), and Lycopersicon (Catalá et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Identifications of IAA conjugates as endogenous substances in vegetative tissues include IAIns in Z. mays (Chisnell, 1984), indole-3-acetylalanine in Picea abies (Ostin et al, 1992b), and IAAsp in P. syluestris (Andersson and Sandberg, 1982), Glycine max (Cohen and Baldi, 1983), and Heracleum laciniatum (Cohen and Ernstsen, 1991). In addition, formation of IAA conjugates has also been demonstrated after exogenous IAA application, and IAAsp appears to be a common product in many species (Riov and Gottlieb, 1980;Monterio et al, 1988;Norcini and Heuser, 1988;Nordstrom et al, 1991). Formation of IAGluc has also been reported after exogenous IAA application (Zenk, 1961;Riov and Gottlieb, 1980;Catali et al, 1992), and recently, an enzyme catalyzing IAGluc synthesis was purified to homogeneity from maize (Komoszynski and Bandurski, 1991).…”
mentioning
confidence: 99%
“…Nordström et al (1991) attributed this preference, relative to IAA, to the higher stability of IBA. On the other hand, in many conifers the cuttings respond well to a pulse treatment with NAA.…”
Section: Auxinsmentioning
confidence: 99%
“…An ATP-binding cassette transporter mediating IAA efflux (ABCB19) has also been linked to adventitious root formation (Sukumar et al, 2013). Other members of the same family have been shown to transport the auxin precursor indole-3-butyric acid (Ruzicka et al, 2010;Strader and Bartel, 2011), which, among all tested auxin isoforms, has the highest competence to induce adventitious root formation (Nordström et al, 1991). Additional hormone signals regulate adventitious roots (Bellini et al, 2014; Fig.…”
Section: Adventitious Rooting In Arabidopsismentioning
confidence: 99%